Effective and Efficient Elementary School Management Strategies - Shinta Aninda Pratiwi; Yustin, Anggia Noorsita; Angellina, Zerra Puspita; Ermawati, Diana (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to analyze the contextual learning process in improving third-grade students’ mathematical problem-solving skills at SDN 2 Mlati Lor on the topic of area and perimeter of plane figures. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The study was conducted in two observation stages, on May 20 and June 2, 2025. The research subjects consisted of 10 students selected purposively based on high, medium, and low ability categories. The results show that the Contextual Teaching and Learning (CTL) approach effectively enhances students’ understanding of area and perimeter concepts. Most students were able to restate concepts, classify objects, and represent mathematical ideas. However, higher-order thinking indicators such as identifying necessary and sufficient conditions still require further reinforcement. These findings indicate that contextual learning is effective in improving students’ problem-solving abilities through real-life experiences relevant to their daily lives.